PELATIHAN PEMBUATAN PUPUK CAMPUR UNTUK BUDIDAYA KELAPA SAWIT PADA FASE MAIN-NURSERY DI KELOMPOK TANI BANGUN BERSAMA: Training For Mixed Fertilizer For Palm Oil Cultivation In Main-Nursery Phase In Bangun Bersama Farmers Group - Nur Ikhsan; Roni ismoyojati (Pakis Journal Institute, 2023)
The scarcity of compound fertilizer that often occurs on the market has caused farmer members who are members of the Bangun Bersama farmer group, Mekar Mulya Village, Sematu Jaya District, Lamandau Regency, Central Kalimantan Province to experience problems applying fertilizer to the oil palm plants they cultivate. In addition, limited information causes a lack of knowledge of members regarding other alternatives that can be used to overcome the scarcity of compound fertilizers, one of which is the single fertilizer mixing technique. The purpose of this service is to improve the skills of the members of the Bangun Bersama farmer group in making mixed fertilizer sourced from a single fertilizer which has an elemental content equivalent to the compound fertilizer recommendation. The service method used is training with lectures and work demonstrations of mixing fertilizers using a single fertilizer containing elements of N, P, K and Mg as well as monitoring the implementation of the training. Based on the results of the PkM activities carried out, it generated new knowledge for the Bangun Bersama farmer group in terms of utilizing single fertilizers into compound fertilizers using mixing techniques.